Effect of ferric hydroxide on membrane fouling in membrane bioreactor treating pharmaceutical wastewater. (November 2019) - Huang, Shujuan; Shi, Xueqing; Bi, Xuejun; Lee, Lai Yoke; Ng, How Yong
Highlights: Membrane fouling rate was reduced by 35% with iron addition. Addition of iron enhanced biomass activity and enlarged flocs size. SMP and DOMs concentrations in mixed liquor reduced remarkably by iron addition. Relative abundance of biofilm-forming related bacteria decreased in Fe-MBR compared with Co-MBR. Abstract: Membrane fouling is considered as a main drawback for MBR technology especially treating industrial wastewater. Therefore, this study aimed to investigate the effect of fouling in membrane bioreactor (MBR) treating pharmaceutical wastewater with the addition of ferric hydroxide. Two identical lab-scale MBRs, namely, a control MBR (Co-MBR) and an enhanced MBR dosed with ferric hydroxide (Fe-MBR), were operated in parallel. The results demonstrate membrane fouling was retarded by 35% with the addition of iron. Further exploration of membrane fouling mechanisms showed iron addition resulted in increase in biomass floc size, enhancement of bacteria activity and reduction of dissolved organic concentration, especially carbohydrate, biopolymer and low molecular weight compounds concentrations in mixed liquor. There was also lower abundance of bacterial associated with biofilm formation in the Fe-MBR compared with the Co-MBR. These findings collectively contributed to the positive impacts on membrane fouling mitigation.